Development, Experimental Assessment, and Application of a Vacuum-Driven Soft Bending Actuator - Goran Gregov; Tonia Vuković; Leonardo Gašparić; Matija Pongrac (Applied Sciences)
This study presents the design, development, and experimental assessment of soft pneumatic actuators for achieving bending motion utilizing vacuum pressure, with their final application to soft robotic grippers. A novel soft actuator design is introduced, satisfying the following design requirements: safe operation without the risk of explosion, the ability to achieve large angular bending while overcoming significant forces, and the use of soft materials that are resistant to material fatigue. A vacuum-driven soft bending actuator (VSBA) was designed, incorporating a cylindrical ribbed bellow geometry and an integrated limiting element within its structure. Two variations of the VSBA were fabricated, each differing in the materials and manufacturing processes employed. The first version employs a cylindrical ribbed bellow made of thermoplastic rubber (TPR), while the other versions utilize heat-shrinkable polymer materials, resulting in an innovative manufacturing process capable of producing actuators in various sizes and shapes. This contributes to the analysis of how actuator geometry affects performance and enables its miniaturization. The performance of the novel VSBAs were experimentally assessed through measuring the bending angle, blocking force, and angular velocity–angle characteristics. The results confirmed a maximum bending angle of 140° corresponding to a bending ratio of 78%, a maximum blocking force of 110 N, and maximum angular velocity of 520°/s at a vacuum pressure of −0.8 bar. Finally, a soft robotic gripper was developed, consisting of three newly designed VSBAs. Experimental assessments demonstrated the gripper’s capability to grasp objects of various shapes, with a maximum holding force of 28 N.